Impact on the Quality of Life of an Educational Program for the Prevention of Work-Related Musculoskeletal Disorders: a randomized controlled trial - Amantéa Vinicius A; Rosa Karen F; Bredemeier Markus; Santos Antonio C; Xavier Ricardo M (BMC, 2011)
Abstract Background Work-related musculoskeletal disorders (WMSD) are a major cause for concern in public health and the main causes of sick leave. Treatments for WMSD have given disappointing results; prevention is the best strategy, but results of preventive measures have not been consistent. To the best of our knowledge there are few studies in literature that evaluated the impact of a specific program aimed at preventing WMSD on the quality of life of employed persons. Methods One hundred and one clerical and production workers in a steel trading company were enrolled in an open-label randomized controlled clinical trial (parallel groups) to compare the efficacy of an educational program for primary prevention of WMSD with control intervention. The primary outcome was a change in the physical functioning domain of the quality of life (QL) measured by Medical Outcomes Study Short Form 36 Health Survey (SF-36). The intervention group underwent six consecutive weekly sessions concerning specific orientations for the prevention of WMSD, while the control group received general health education in an identical schedule. The SF-36 and theses Work Limitation Questionnaire (WLQ) were evaluated at weeks zero, five and 26. Results Baseline characteristics of the interventions groups were comparable, and both groups comprised predominantly young healthy individuals. No significant differences in the variation of the SF-36 and WLQ between the groups were observed at weeks five and 26. However, both groups demonstrated improvement in some aspects of SF-36, suggesting that both educational interventions have beneficial impacts on QL. Conclusions A specific educational program aimed at the preventing of WMSD was comparable with general health orientation for the improvement of QL and work capacity in a sample of healthy workers during a six month period. Trial Registration ClinicalTrials.gov: NCT00874718 Trial Registration